RESTRUKTURISASI PEMBIAYAAN SEBAGAI SALAH SATU UPAYA PENANGANAN PEMBIAYAAN BERMASALAH - Trisadini Prasastinah Usanti (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2006)
Financing given by syaria banking always has potensial risk of repayment failure which causes non performing financing. Attemps from syaria banking to resolve non performing financing are principally the same with conventional banking. Those attemps are such as: financing restructure, collateral execution, through litigation, through board of arbitration national syaria, write off and hair cut.